Emotion-related theories in classroom language learning: the conceptualization and causation of emotions - Wu, Wenjie; Kabilan, Muhammad Kamarul (Frontiers in Psychology, 2025)
Language classrooms are embedded with a wide range of emotions. Emotions play a significant role in affecting learners' language learning and academic performance. Yet, while the role of emotions in L2 classrooms has been recognized, very scant studies have investigated the underlying theoretical frameworks in great depth with regard to the conceptualization and causation of emotions. Moreover, very few review studies have paid sufficient attention to the antecedents or causes of emotions underpinned by certain theories in the field of SLA. Therefore, to offer a complementary review of emotion-related theories and provide fresh insights into the emotional research in SLA, the present study first explains the theoretical approaches of the conceptualization and causation of emotions, elucidates how these theories are applied into the emotional research in language learning, and identifies the effect of the interplay between cognitive, psychological, social, and contextual factors on the emotional development in the language learning. Finally, practical implications, like emotional regulation strategies for both language teachers and learners and future directions, like the integration with AI tools for L2 researchers, language teachers, and teacher educators who are interested in emotional research are also discussed.